Accounting for Expected Cost Savings and Synergy Gains: The Role of Lenders’ Risk Preferences - Jiang, Shushu (Contemporary Accounting Research, 2026)
ABSTRACT This paper examines whether lenders' risk preferences explain the use of cost‐synergy adjustments in loan contracts. These adjustments represent an aggressive accounting choice that permits borrowers to add expected cost savings and synergy gains from mergers, acquisitions, and restructurings to contractual earnings. Using novel data from loan contracts, I first document an increasing prevalence of these adjustments over the past two decades. Consistent with the notion that these adjustments provide borrowers with greater risk‐taking flexibility and increase the riskiness of lenders' payoffs, I find that lenders with stronger risk‐taking preferences are more likely to use these adjustments. This finding is more pronounced when lenders face lower monitoring costs and when borrowers are led by managers who are less risk‐incentivized. It is also stronger in loan contracts that grant borrowers more flexibility through these adjustments and when lenders face greater pressure to reach for yield. Overall, my findings highlight the importance of lenders' risk preferences in determining accounting choices in debt contracting.